Internalisasi Karakter Religius Dan Kepemimpinan Siswa Melalui Kegiatan Pramuka Di Sekolah Dasar Islam Surabaya - Wahzudi, Muhammad; Ariyansyah, Zuhal (Tarunateach: Journal of Elementary School, 2024)
This research is motivated by the rapid development of technology and information today, both from social media or other media, so it is necessary to internalize religious and leadership characters as a foundation so as not to be negatively affected by these developments and as an altenative media, namely through scouting activities. This study aims to analyze the process, supporting and inhibiting factors for internalizing the religious character and leadership of students through scouting activities at SDI Miftahul Ulum Surabaya. This type of research is descriptive qualitative. The research was conducted at SDI Miftahul Ulum Surabaya. The data collection techniques used included interviews, observation, and documentation. After the data is collected, the next step is to clarify the data according to the problem formulation, then analyze the data using descriptive analysis techniques, so that a research finding is drawn. The results of this study are: 1) Internalization of the religious character of students through scout activities at SDI Miftahul Ulum Surabaya is carried out in three ways, namely aspects of aqidah (belief), sharia (religious practice), and akhlaq. 2) Internalization of the student's leadership spirit through scouting activities at SDI Miftahul Ulum Surabaya is carried out in three ways, namely multiplying self-potential, organizing (groups), and management (processing / managing).3) Supporting factors and inhibiting internalization of religious character and student leadership through There are four things in scouting activities at SDI Miftahul Ulum Surabaya, namely the support of the principal and parents of students, enthusiasm of students in participating in scouting activities, inadequatefacilities and very limited scout training time.